Carbon nanotube–ionic liquid composite gel based high-performance bioanode for glucose/O2 biofuel cells. Issue 12 (21st June 2015) - Sun, Longfei; Zhang, Xiaohua; Wang, Wenyang; Chen, Jinhua
<x xml:space="preserve">Abstract</x> An easy-operation and high-performance bioanode based on a composite gel of ferrocenecarboxaldehyde modified CNTs and an ionic liquid was successfully developed.